hERG K+ channel-associated cardiac effects of the antidepressant drug desipramine - Staudacher, Ingo; Wang, Lu; Wan, Xiaoping; Obers, Sabrina; Wenzel, Wolfgang; Tristram, Frank; Koschny, Ronald; Staudacher, Kathrin; Kisselbach, Jana; Koelsch, Patrick; Schweizer, Patrick Alexander; Katus, Hugo; et al. (Naunyn-Schmiedeberg's archives of pharmacology, 2011)
Cardiac side effects of antidepressant drugs are well recognized. Adverse effects precipitated by the tricyclic drug desipramine include prolonged QT intervals, torsade de pointes tachycardia, heart failure, and sudden cardiac death. QT prolongation has been primarily attributed to acute blockade of hERG/IKr currents. This study was designed to provide a more complete picture of cellular effects associated with desipramine. hERG channels were expressed in Xenopus laevis oocytes and human embryonic kidney (HEK 293) cells, and potassium currents were recorded using patch clamp and two-electrode voltage clamp electrophysiology. Ventricular action potentials were recorded from guinea pig cardiomyocytes. Protein trafficking and cell viability were evaluated in HEK 293 cells and in HL-1 mouse cardiomyocytes by immunocytochemistry, Western blot analysis, or colorimetric MTT assay, respectively. We found that desipramine reduced hERG currents by binding to a receptor site inside the channel pore. hERG protein surface expression was reduced after short-term treatment, revealing a previously unrecognized mechanism. When long-term effects were studied, forward trafficking was impaired and hERG currents were decreased. Action potential duration was prolonged upon acute and chronic desipramine exposure. Finally, desipramine triggered apoptosis in cells expressing hERG channels. Desipramine exerts at least four different cellular effects: (1) direct hERG channel block, (2) acute reduction of hERG surface expression, (3) chronic disruption of hERG trafficking, and (4) induction of apoptosis. These data highlight the complexity of hERG-associated drug effects.